Development and utility of online knowledge repository of safflower (Carthamus tinctorius L.) in Agropedia platform: DEVELOPMENT AND UTILITY OF ONLINE KNOWLEDGE REPOSITORY OF SAFFLOWER - P PADMAVATHI (Journal of Oilseeds Research, 2014)
The development of safflower (Carthamus tinctorius) knowledge repository in the larger platform of Agropedia is discussed in this paper. Agropedia is an open platform which facilitates exchange and delivery of information between the agricultural community through a web portal and mobile phone networks accessible to phones with limited data capability. The reasons and requirements for development of such web portal in general and safflower in particular and the requirement of semantic search in Agropedia were discussed. Safflower knowledge model is one among different knowledge models of cereals, pulses and horticultural crops. The need for development of safflower knowledge model and different steps involved in development, different methods of searching the content were discussed. Extension workers can access the content available in Agropedia web portal to advise the farmers with respect to improved technologies in safflower cultivation for obtaining higher crop productivity.